On Subjective Ego and Western Philosophy of Amina Wadud’s Misconceptions on Islamic Law - Muhammad Rusydianta (TSAQAFAH, 2026)
This article aims to identify the synthesis or any underlying and background factors that inform Wadud’s thought and her justification, specifically the bases of understanding and thought patterns that influence and shape her perspective and justifications in the Women’s Reform Movement, which deconstructed the Sharia of Allah. From this, muslims can learn to be vigilant and avoid, and realise the importance of educational support for Muallaf not to be influenced by any destructive ideas, environments, and thoughts about religion, themselves, and the muslim community. Therefore, as a type of library research and critical study, this research also utilises secondary materials and data from several documents that explain the object. Primarily, primary data came from historiography and Wadud’s explicit and implicit confessions in her works. The multiple data obtained were processed, analysed, and presented descriptively and qualitatively in line with the main theme of the discussion. Finally, concluded that the synthesis of its movement is the crystalisation of the arrangement of the basic thought patterns of Critical Legal Studies (CLS) and Legal Feminist, combined with her missunderstanding in distinguishing legal term, along with other bases of understanding and justification such as her subjective ego derived from the accumulation of her life experiences and the synthesis of thoughts from certain figures on Sufism, liberal and anti-discrimination movements, chistian, secular Jewish philosophers, lesbian feminist political to other hermeneutic (Fazlur Rahman). Academic anxiety, as she admitted, is not the only basis for her movement to deconstruct Sharia through hermeneutics or feminism.